Prevalence of Low Birth Weight in Urban Dhaka and its Association with Maternal Age and Socioeconomic Status - Razia Shaheen; Medha Roy; Aklima Anny; Nelufa Yeasmin Shova; Tasmia Hema (Dr. Sulaiman Al Habib Medical Journal)
Low Birth Weight (LBW) is a major risk factor for neonatal and infant mortality worldwide. In 2015, the LBW rate was 22.6% in Bangladesh. The present study was conducted to estimate the rate of LBW in urban Dhaka and to observe its association with maternal age and socioeconomic status. This retrospective study was carried out at selected hospitals in Dhaka City. Birth weight, type of facility, mode of delivery and age of mothers of 736 babies born from 2014 to 2016 were collected from the recorded database of these facilities. Frequency analysis, bivariate analysis, with Chi-square test (χ2) and Pearson’s correlation were conducted as test of significance. The prevalence of LBW was 30.2% in Dhaka City, and the mean birth weight of neonates was 2.65 kg. The results of the study indicated that at least three children in every 10 live births are born with LBW in urban Dhaka. Younger maternal age (≤19 years) was significantly associated with LBW (p = 0.020). Pearson’s correlation found a weak positive linear relationship between mother’s age and birth weight of babies (r = 0.108; p = 0.01). Neonates from government facilities, representing the lower socioeconomic group, had a significantly higher LBW rate. The findings of the study will help to initiate preventive programs and to develop public health nutrition interventions to reduce LBW in Bangladesh.